(untitled) (KULT_online, 2017)
Baer and Sznaider’s volume Memory and Forgetting in the Post-Holocaust Era: The Ethics of Never Again furthers memory studies’ global and transnational turn. Its three case studies of post-dictatorial societies focus on memory’s role in democratic transition in Argentina, Spain, and Eastern Europe. These chapters come between broader essays on the “ethics of Never Again” and “sociology of hope”. The authors present Holocaust memory as the universal foundation of human rights, while exploring its complex entanglements with particular, often nationally-bound, memories of victimhood. Unlikely to appeal to readers unfamiliar with debates over cosmopolitan memory, the book’s essayistic elements could stimulate further critical discussion on relations of memory, history, ethics, and the global among the informed.